Invited commentary: hypertension during pregnancy and offspring microvascular structure—insights from the retinal microcirculation - Huckstep, O; Lewandowski, A; Leeson, P (Oxford University Press, 2016)
Human clinical studies as well as laboratory animal studies demonstrate that offspring of pregnancies affected by common complications, such as preeclampsia and preterm birth, display developmental phenotypes that relate distinctly to the pregnancy disorder. Several studies have now found microvascular differences in offspring of hypertensive pregnancies, and there is interest in whether these may underlie epidemiologic associations between gestational hypertension and a higher risk of hypertension and stroke in the offspring. The retinal circulation provides a unique window into microvascular structure, of likely relevance to both the cerebrovasculature and broader cardiovascular risk. Yesil et al. (Am J Epidemiol. 2016;184(9):605-615) report in this issue of the Journal that maternal gestational blood pressure elevation is associated with reduced retinal vascular caliber in offspring at 6 years of age, providing a link between variation in pregnancy characteristics and childhood vascular development. Further work to understand the longitudinal association between pregnancy, emergence of microvascular changes, and cardiovascular risk may identify opportunities for future preventive interventions.